Identification of a melting type variant among peach (P. persica L. Batsch) fruit textures by a digital penetrometer. Issue 4 (3rd January 2018) - Ciacciulli, Angelo; Chiozzotto, Remo; Attanasio, Giovanna; Cirilli, Marco; Bassi, Daniele
Abstract: The increase of peach ( Prunus persica L. Batsch) fruit shelf‐life is one of the most important objectives of breeding activities, as peach is a highly perishable fruit which undergoes rapid softening during ripening. The loss of fruit firmness is accompanied by a modification of textural properties. At least four distinct textures were described in peach: melting, non‐melting, stony‐hard, and slow‐melting (better defined as "slow‐softening"). Flesh textures are usually discriminated using different approaches, specific for each type. Objective of this work was the development of a reliable method to assess flesh texture variants in peach fruit, with special attention to the slow‐softening type which is currently scored by sensorial evaluation. A puncture‐based test using a digital penetrometer was performed on 20 accessions belonging to the four textural groups, obtaining a series of rheological measures related to mechanical flesh properties and including Young's Modulus, Upper Yield Point, and Slope of Yield Stress. Among the components of elasto‐plastic behavior of the fruits, the texture dynamic index (TD) was shown to be a reliable parameter to distinguish the group of melting flesh texture from slow‐softening, non‐melting, and stony‐hard, these last resulting characterized by similar mechanical properties. The TD index can be applied to discriminate slow‐softening and melting fruits, although variability within the different texture groups suggests the existence of accessions with intermediate phenotypes and minor quantitative trait variation. The availability of an objective method to clearly distinguish the melting from the slow‐softening phenotypes paves the road to phenotype segregating progenies in order to find molecular markers associated to the slow‐softening trait. Practical applications: The TD index could be considered to determine different textures in fleshy fruits in preharvest and postharvest, to support evaluation of quality for the intended use.